2018
DOI: 10.1159/000493364
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetic Study of Mangiferin in Normal and Alloxan-Induced Diabetic Rats after Oral and Intravenous Administration by UPLC-MS/MS

Abstract: Backgrounds: Diabetes mellitus (DM)-induced morphological and/or functional complications may alter the pharmacokinetic profiles of mangiferin. This study aims to compare pharmacokinetic profiles of mangiferin in normal and alloxan-induced diabetic rats after oral and intravenous administration. Methods: Mangiferin was administered orally (10 mg/kg) and intravenously (2 mg/kg) to normal and alloxan-induced diabetic Sprague-Dawley (SD) rats (n = 8). Blood samples were collected at different time points post-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
2
2
0
1
Order By: Relevance
“…The reasons for these discrepancies could be attributed to the changed activity of drug‐metabolizing enzymes and drug transporters under the pathological state of diabetes mellitus [26, 38, 39]. This is in accordance with several publications showing that diabetes mellitus significantly altered the pharmacokinetic characteristics of drugs in vivo [11, 40, 41]. Results presented a meaningful basis for the clinical applications of R. vomitoria when used in the treatment of diabetes mellitus.…”
Section: Resultssupporting
confidence: 80%
“…The reasons for these discrepancies could be attributed to the changed activity of drug‐metabolizing enzymes and drug transporters under the pathological state of diabetes mellitus [26, 38, 39]. This is in accordance with several publications showing that diabetes mellitus significantly altered the pharmacokinetic characteristics of drugs in vivo [11, 40, 41]. Results presented a meaningful basis for the clinical applications of R. vomitoria when used in the treatment of diabetes mellitus.…”
Section: Resultssupporting
confidence: 80%
“…Further context in terms of the present results and previous cell-based studies is the confirmed low oral bioavailability and tissue disposition of many dietary polyphenols (i.e., their tendency to not reach target tissues at the required concentrations following interaction with microbiota, absorption, and phase II metabolism) [27]. For example, oral bioavailability of mangiferin in normal and alloxan-induced diabetic rats amounted to just 1.71 % and 0.80 %, respectively [28], while the peak plasma concentra-▶ Table 1 Apparent permeability coefficients and efflux ratios for the 2 major xanthones, mangiferin and isomangiferin, and the 2 major benzophenones, IDG and I3G, in Cyclopia genistoides fractions, tested individually or in combination, for ex vivo intestinal permeability.…”
Section: Resultssupporting
confidence: 76%
“…Even though there are very significant potential health benefits of mangiferin, this compound shows substantial restrictions for its clinical use in cancer management due to poor water solubility, low absorption and rapid elimination [124]. Mangiferin led to an exhaustive hepatic first-pass metabolism, reducing the fraction of the dose reaching the systemic circulation, which is a reason causing the low oral bioavailability, leading to limitation of the efficacy [125]. An HPLC/MS method for the measurement of mangiferin in rat plasma was performed.…”
Section: Conclusion Challenges and Future Prospectivementioning
confidence: 99%